The Preparation and Electrochemical Pseudocapacitive Performance of Mutual Nickel Phosphide Heterostructures - Shao-Bo Guo; Wei-Bin Zhang; Ze-Qin Yang; Xu Bao; Lun Zhang; Yao-Wen Guo; Xiong-Wei Han; Jianping Long (Crystals, 2022)
Transition metal phosphide composite materials have become an excellent choice for use in supercapacitor electrodes due to their excellent conductivity and good catalytic activity. In our study, a series of nickel phosphide heterostructure composites was prepared using a temperature-programmed phosphating method, and their electrochemical performance was tested in 2 mol L−1 KOH electrolyte. Because the interface effect can increase the catalytic active sites and improve the ion transmission, the prepared Ni2P/Ni3P/Ni (Ni/P = 7:3) had a specific capacity of 321 mAh g−1 under 1 A g−1 and the prepared Ni2P/Ni5P4 (Ni/P = 5:4) had a specific capacity of 218 mAh g−1 under 1 A g−1. After the current density was increased from 0.5 A g−1 to 5 A g−1, 76% of the specific capacity was maintained. After 7000 cycles, the capacity retention rate was above 82%. Due to the phase recombination effect, the electrochemical performance of Ni2P/Ni3P/Ni and Ni2P/Ni5P4 was much better than that of single-phase N2P. After assembling the prepared composite and activated carbon into a supercapacitor, the Ni2P/Ni3P/Ni//AC had an energy density of 22 W h kg−1 and a power density of 800 W kg−1 and the Ni2P/Ni5P4//AC had an energy density of 27 W h kg−1 and a power density of 800 W kg−1.